Transcriptional and metabolic alternations rebalance wheat grain storage protein accumulation under variable nitrogen and sulfur supply. (8th June 2015) - Dai, Zhanwu; Plessis, Anne; Vincent, Jonathan; Duchateau, Nathalie; Besson, Alicia; Dardevet, Mireille; Prodhomme, Duyen; Gibon, Yves; Hilbert, Ghislaine; Pailloux, Marie; Ravel, Catherine; Martre, Pierre
Summary Wheat (Triticum aestivum L.) grain storage proteins (GSPs) are major determinants of flour end‐use value. Biological and molecular mechanisms underlying the developmental and nutritional determination of GSP accumulation in cereals are as yet poorly understood. Here we timed the accumulation of GSPs during wheat grain maturation relative to changes in metabolite and transcript pools in different conditions of nitrogen (N) and sulfur (S) availability. We found that the N/S supply ratio modulated the duration of accumulation of S–rich GSPs and the rate of accumulation of S–poor GSPs. These changes are likely to be the result of distinct relationships between N and S allocation, depending on the S content of the GSP. Most developmental and nutritional modifications in GSP synthesis correlated with the abundance of structural gene transcripts. Changes in the expression of transport and metabolism genes altered the concentrations of several free amino acids under variable conditions of N and S supply, and these amino acids seem to be essential in determining GSP expression. The comprehensive data set generated and analyzed here provides insights that will be useful in adapting fertilizer use to variable N and S supply, or for breeding new cultivars with balanced and robust GSP composition.